To Determine the Effect of Diabetes Mellitus on the Clinical Course and Outcome of COVID-19 at Jinnah Hospital, Lahore, - Muhammad Aleem, Sadia Salman, Javeid Iqbal, Muhammad Zaeem Khalid, Amna Riaz, Hafiz Abdul Rauf, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes is a common disease known to cause morbidity and mortality. Individuals with diabetes are at greater risk of complications from coronavirus and have recently gains attention of researchers and practitioners. Aim: To assess the effect of diabetes mellitus on clinical course and outcome of coronavirus infection. Study design: Prospective cohort study Place and duration of study: Coronavirus Disease High Dependency Unit Jinnah Hospital, Lahore from 01-01-2021 to03-04-2021. Methodology: Three hundred and seventy six patients of either genders and age range of 15-75 years were enrolled. They were divided into diabetic or non-diabetic groups. The various attributes such as demographic data, medical history, COVID-19 exposure history, symptoms and signs, laboratory findings, chest radiograph findings, the treatment measures and complications of diabetes and in hospital outcome were compared for both the groups. Result: Statistically different from each other in terms of oxygen requirement, lymphocyte %, neutrophil to lymphocyte ratio (P=0.026), alanine aminotransferase (P=0.038), C-reactive protein (P=0.048), ferritin (P=0.031), lactic acid dehydrogenase (LDH) (P=0.011), D-dimer (P=0.024), Quick sequential organ failure assessment score (qSOFA score) (P=0.001) and Chest X-ray (P=0.049), blood sugar random (P=0.000), treatment during hospital stay (P=0.000), insulin dose increase (P=0.000), complications during hospital stay (P=0.042) and shifting to the intensive care unit (P=0.002). Conclusion: Diabetic coronavirus patients have poorer prognosis due to higher risk of severe pneumonia and related complications including mortality than their non-diabetic counterparts.